Pemakaian Umpatan dalam Bahasa Luwu pada Mahasiswa IPMIL Raya Unhas: Kajian Sosiolingustik - Asria Sadda; Muhlis Hadrawi; Muhammad Nur (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2022)
This research was inspired by the phenomenon of curse words use in Tana Luwu which its region has special dialect or language variety. This research aimed to describe forms and functions of curse words used in the form language in Tana Luwu. The present research was sourced from students from Tana Luwu who join Student Association of Luwu in Hasanuddin University. This research used descriptive method with qualitative analysis. The research results showed that curse words used in the form of language in Tana Luwu refer to seven references, namely animal, body parts/condition of body parts, impurity, supernatural creatures, diseases, adjectives, and condition. Meanwhile, the functions of the term are classified into four things, namely as the expression of annoyance, anger and exasperation, as greeting to be intimate, as expression of condition suddenly occurring, or unexpectedly happening, and as a form of satire.